Optimization of Geopolymer Compressive Strength Using Response Surface Methodology - Cut Rahmawati (LPPM Politeknik Aceh Selatan, 2023)
Geopolymers have issues related to cracking resistance and pore filling, decreasing their mechanical strength. However, the addition of nanosilica and Cellulose Nanocrystals (CNCs) has been found to enhance their mechanical properties. This study focused on optimizing the utilization of nanosilica and CNCs to enhance the compressive strength of geopolymers. This research employed Response Surface Methodology (RSM) with Central Composite Design (CCD). The concentrations of nanosilica and CNCs used in the experiments ranged from 2% to 4% and 1% to 3%, respectively. The experimental results consist of 13 runs, including 5 center point runs. The model suggested concentrations of nanosilica and CNCs of 3.98% and 1%, respectively, for an optimal compressive strength of 22.20 MPa. The proposed quadratic model exhibited high accuracy, as evidenced by an R2 of 0.9865, Adj- R2 of 0.9769, and predicted R2 of 0.9168. The closeness of R2 to 1 indicates a strong correlation between the actual and predicted values, thus highlighting the model's significant relevance. Ultimately, the model developed in this study holds the potential for predicting the compressive strength of geopolymers incorporating nanosilica and CNCs.